Quality Assurance of Academic Websites using Performance Testing Tools - Fifin Ayu Mufarroha,; Ahmad Farisul Haq,; Arifatul Maghfiroh,; Devie Rosa Anamisa,; Ahmad Afif Supianto,; Achmad Jauhari, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Academic websites play a crucial role in supporting learning activities and academic growth in the digital age. These websites are created and maintained by academic institutions to provide resources, services, and information to the academic community. Academic websites aim to promote the institution, facilitate communication, and disseminate educational content. However, as these websites develop in complexity and draw more visitors, it is crucial to guarantee their efficient operation and satisfying user experience. For academic websites to operate and be reliable, top-notch software development and thorough software testing are required. The performance testing of academic websites using Apache JMeter and the Web Server Stress Tool is the main topic of this study. This study's conclusions are intended to improve software quality and performance for academic website managers and developers. Gathering data, establishing the test environment, planning and creating the test, carrying it out, and evaluating the system in light of the test results are all steps in the performance testing process. The website operates well under heavy traffic, according to the findings of the performance testing done with Apache JMeter. However, the Web Server Stress Tool shows that the website's performance is insufficient under significant user loads. This test gives information about the website's functionality and any potential problems, which can then be used to determine whether speed improvements are required.